Developing a scale measuring customers' servicescape perceptions in upscale hotels. Issue 1 (13th January 2020) - Lockwood, Andrew; Pyun, Kyunghee
Abstract : Purpose: This paper aims to describe the detailed process of development of a reliable scale to measure customer perceptions of the upscale hotel servicescape that could then be used as a basis for intra- and inter-hotel comparisons and to examine relationships with other variables, such as emotions, satisfaction and loyalty. Design/methodology/approach: A review of the existing service and hospitality literature provided a range of dimensions and attributes of the hotel servicescape, which were used as the basis for a Q-sort technique to determine the content adequacy of newly developed and existing items. Testing the emergent items was carried out through a questionnaire that was distributed at five luxury upscale hotels in London providing 612 fully valid responses, which, using a split sample, were subjected to both exploratory and confirmatory factor analyses to explore the dimensionality and reliability of the instrument. Findings: Although the Q-sort suggested four key dimensions, the outcome of the factor analyses revealed five dimensions with high reliability – aesthetic quality, functionality, atmosphere, spaciousness and physiological conditions. "Aesthetic quality" appeared to be the most important factor, followed by "functionality", "atmosphere", "spaciousness" and "physiological conditions". Research limitations/implications: As this study was conducted with customers of upscale luxury hotels in London, the resulting scales need to be further tested in other hotel segments and in other locations. Practical implications: This study provides upscale hotel managers with an effective measurement tool, which will enable them to benchmark their operation and make improvements that could lead to a better impression and evaluation of their hotel. The scale has a variety of potential applications and can serve as a framework for further research in the hotel industry. Originality/value: In spite of the wide interest in and importance of the servicescape in hotels, there are only a few studies dealing with this subject in the hotel context. This study provides a new tool for measuring customers' perceptions.